Parvovirus 4 infection and clinical outcome in high-risk populations - Simmons, R; Sharp, C; Rohrbach, J; Kovari, H; Frangou, E; Simmonds, P; Irving, W; Rauch, A; Bowness, P; Klenerman, P; Swiss HIV Cohort Study (Oxford University Press, 2012)
Parvovirus 4 (PARV4) is a DNA virus frequently associated with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections, but its clinical significance is unknown. We studied the prevalence of PARV4 antibodies in 2 cohorts of HIV- and HCV-infected individuals (n = 469) and the correlations with disease status. We found that PARV4 infection frequently occurred in individuals exposed to bloodborne viruses (95% in HCV-HIV coinfected intravenous drug users [IDUs]). There were no correlations between PARV4 serostatus and HCV outcomes. There was, however, a significant association with early HIV-related symptoms, although because this was tightly linked to both HCV status and clinical group (IDU), the specific role of PARV4 is not yet clear.